Pengaruh Terapi Slow Stroke Back Massage terhadap Tekanan Darah pada Pasien Hipertensi di Ruangan Pulau Selayar RSAL Dr. Mintohardjo Jakarta Pusat 2023 - Savira Auliyah; Nur Eni Lestari; Emi Yuliza (Jurnal Medika Nusantara, 2024)
Hypertension is a health problem that is quite dangerous throughout the world because it leads to cardiovascular diseases such as heart attacks, heart failure, stroke and kidney disease and is the two main causes of death in the world. To deal with the effects of hypertension, treatment must be carried out early using pharmacological and non-pharmacological treatments. One of the non-pharmacological efforts to treat hypertension is massage therapy. The aim of this study was to determine the effect of slow stroke back massage therapy on blood pressure in hypertensive patients in the Selayar Island Room at RSAL Dr. Mintohardjo, Central Jakarta. This research uses a pre-experimental design research type with a one group pretest-posttest design approach. The sample used was 20 people using an accidental sampling technique. Data collection uses observation sheets. The results of this study show that there is a difference in systolic blood pressure before and after slow stroke back massage therapy with a value of ?=0.000 and there is a difference in diastolic blood pressure before and after slow stroke back massage therapy with a value of ?=0.010. The conclusion of this study is that there is an effect of slow stroke back massage therapy on blood pressure in hypertensive patients in the Selayar Island Room at RSAL Dr. Mintohardjo, Central Jakarta.